The Effect of the Dietary Approaches to Stop Hypertension (DASH) Diet on Sleep, Mental Health, and Hormonal Changes: A Randomized Clinical Trial in Women With Type 2 Diabetes - Daneshzad, Elnaz; Heshmati, Javad; Basirat, Vahid; Keshavarz, Seyed-Ali; Qorbani, Mostafa; Larijani, Bagher; Bellissimo, Nick; Azadbakht, Leila (Frontiers in Nutrition, 2022)
Background. Some dietary patterns may improve diabetes complications through scavenging oxidants and anti-inflammatory properties. This study evaluated the effect of the Dietary Approaches to Stop Hypertension (DASH) diet on sleep status, mental health, and hormonal changes among Iranian women with type 2 diabetes. Methods. This randomized controlled trial (RCT) included 66 diabetic women. Participants were randomly divided into two different diet groups (DASH diet and control diet; 33 patients in each group) for 3 months. The Pittsburgh Sleep Quality Index and 21 items Depression, Anxiety, and Stress Scale were used to assess sleep and mental disorders, respectively. Fasting blood sugar, hemoglobin A1c (HbA1c), advanced glycation end products (AGEs), as well as several sex hormones were evaluated at the beginning and the end of the trial. Results. Anthropometric indices, HbA1c (control: 8.77 ± 0.82 vs. 8.04 ± 1.03; DASH diet 8.70 ± 1.05 vs.7.41 ± 1.03), and follicle-stimulating hormone (FSH) (control: 72.16 ± 26.02 vs. 68.12 ± 27.63; DASH diet: 72.99 ± 25.19 vs. 67.43 ± 27.63) significantly decreased over 12 weeks in both groups (P< 0.0001). Testosterone, 2-h postprandial glucose, and AGEs significantly decreased over 12 weeks in the DASH diet group. Sleep, depression, and anxiety scores significantly decreased over 12 weeks in the DASH diet group. Night sleep duration significantly increased over 12 weeks in the DASH diet group (P<0.0001). Conclusion. A 12-week DASH diet significantly decreases testosterone, 2-hppG, AGEs level, as well as sleep, depression, and anxiety scores in women with type 2 diabetes. However, more RCTs are needed to confirm these findings.